New insights into the pathogenesis of autosomal-dominant cutis laxa with report of five ELN mutations - Callewaert, Bert; Renard, Marjolijn; Hucthagowder, Vishwanathan; Albrecht, Beate; Haußer-Siller, Ingrid; Blair, Edward; Dias, Cristina; Albino, Alice; Wachi, Hiroshi; Sato, Fumiaki; Mecham, Robert P.; Loeys, Bart; et al. (Human mutation, 2011)
Autosomal dominant cutis laxa (ADCL) is characterized by a typical facial appearance and generalized loose skin folds, occasionally associated with aortic root dilatation and emphysema. We sequenced exons 28-34 of the ELN gene in five probands with ADCL features and found five de novo heterozygous mutations: c.2296_2299dupGCAG (CL-1), c.2333delC (CL-2), c.2137delG (CL-3), c.2262delA (monozygotic twin CL-4 and CL-5), and c.2124del25 (CL-6). Four probands (CL-1,-2,-3,-6) presented with progressive aortic root dilatation. CL-2 and CL-3 also had bicuspid aortic valves. CL-2 presented with severe emphysema. Electron microscopy revealed elastic fiber fragmentation and diminished dermal elastin deposition. RT-PCR studies showed stable mutant mRNA in all patients. Exon 32 skipping explains a milder phenotype in patients with exon 32 mutations. Mutant protein expression in fibroblast cultures impaired deposition of tropoelastin onto microfibril-containing fibers, and enhanced tropoelastin coacervation and globule formation leading to lower amounts of mature, insoluble elastin. Mutation-specific effects also included endoplasmic reticulum stress and increased apoptosis. Increased pSMAD2 staining in ADCL fibroblasts indicated enhanced transforming growth factor beta (TGF-β) signaling. We conclude that ADCL is a systemic disease with cardiovascular and pulmonary complications, associated with increased TGF-β signaling and mutation-specific differences in endoplasmic reticulum stress and apoptosis.
Gesehen am 27.06.2022